(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2019)
There are numerous studies that support the interest of starting the development of algebraic thinking in Primary School. In this paper, we present a part of a research project aimed to explore the processes of solution of geometric pattern problems by students in Primary grades 4th to 6th. We analyze the behavior of students who were administered a teaching unit based on the resolution of this type of problems in the GeoPattern application, created by the authors for this purpose. A characteristic of the application is that it informs the students on the correctness of their answers and allows them to respond again to the same question when their answer was wrong. This causes the students to initiate self-correction processes. We describe the different types of behavior we have identified in students whose answer to a question was wrong and they tried to solve it again.